The Impact of Collective Nostalgia on Architectural Characteristics of Shrine Buildings - Armange Ismael Barakat; Alan Faraydoon Ali (Journal of Studies in Science and Engineering)
Nostalgia, in psychology, is an emotional state, while socially and culturally, it embodies a society's collective memory and heritage. In architecture, nostalgia refers to the emotional and cultural bond people have with the past, expressed through built environments that evoke shared memories and meanings. This study aims to define nostalgia within an architectural context and investigate how it influences architectural features, particularly in shrine buildings. The research investigates the influence of collective nostalgia on design characteristics, adopting a five-phase mixed-methods approach. The first phase involves constructing a theoretical framework and identifying indicators of collective nostalgia. In the second phase, expert interviews with specialists in literature, sculpture, psychology, and architecture are used to validate the reliability of these indicators. The third phase consists of a questionnaire survey to refine and prioritize the most relevant indicators. The fourth phase applies the validated model to case study analysis, and the fifth phase performs statistical analysis to identify correlations between variables. The results demonstrate that collective nostalgia has a significant impact on architectural function, resulting in a unique architectural expression characterized by commemorative shrines. Additionally, collective nostalgia shapes symbolic and sculptural elements within architectural forms, reinforcing cultural identity and emotional connection through design.